EVALUASI KINERJA GURU RUMPUN PAI DI MADRASAH IBTIDAIYAH NEGERI 2 TANJUNG BERINGIN KABUPATEN KAUR - Intan Utami (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2018)
This study aims to determine the performance evaluation PAI clumps in the planning,  implementation and  evalua- tion of learning in the State Islamic Elementary School (MIN) Tanjung  Beringin District Kaur. These types of research, including research  evaluation, data  collection method in this research  is to use the techniques of observation, interviews, questionnaires and  documentation. The conclusion  of this paper  that the teacher  performance MIN 2 Tanjung  Beringin clumps of PAI in the planning  of the learning process quite well. Planning  is used in learning is always made  at the beginning  of the semester.  How- ever, there are weaknesses in the preparation of the plan, namely the lack of planning  time is written in the plan, structuring the learning  background, development of instructional  media  and  learning  resources  are not well planned. 2 MIN teacher  perfor- mance  Tanjung  Beringin clump PAI has been  good  and  in accordance with the regulations, both  in the open  class, delivering course  material,  using teaching  methods, using instructional  media,  classroom  management and  lesson closes. 2 MIN teacher performance Tanjung  Beringin  clump  PAI is good  enough to evaluate  conformity  with the  provisions.  Planned evaluation conducted by the teacher  MIN 2 Tanjung  Beringin already  accommodated in the lesson plan, so already  scheduled. But for the evaluation that is impromptu, its implementation depends on the purpose of the material  being taught